Determining strength training needs using the force-velocity profile of elite female handball and volleyball players - Petridis, L.; Pálinkás, G.; Tróznai, Z.; Béres, B.; Utczás, K. (International Journal of Sports Science & Coaching, 2021)
The aim of this study was to assess the vertical jump performance and the force-velocity profile of elite female handball and volleyball players. Forty-one female athletes were measured, 28 handball players (age: 24.0 ± 3.6 years, body height: 1.75 ± 0.05 m, body mass: 69.0 ± 7.3 kg) and 13 volleyball players (age: 24.1 ± 5.2 years, body height: 1.83 ± 0.07 m and body mass: 74.9 ± 7.9 kg). All players performed unloaded and loaded countermovement jumps (CMJ) on a force platform. The theoretical maximal force (F0), the theoretical maximum velocity (v0), the theoretical maximal power (Pmax), the slope of the F-v relationship (Sfv) and the force-velocity imbalance (FVimb) were calculated. Mean value of vertical jump height was 0.33 ± 0.03m, with no difference between handball and volleyball players. Mean values of F0, v0, Pmax, Sfv and FVimb for all players were 31.2 ± 2.6 N/kg, 3.10 ± 0.50 m·s-1, 24.2 ± 3.2 w/kg, -10.32 ± 2.09 Ns/m/kg and 28.1 ± 13.3% respectively. Two players had a low magnitude velocity-deficit, whereas most of the players exhibited a low to high force-deficit. A strong correlation was found between the ratio of measured to optimal F-v slope with the change in the proportion of net force to total force during unloaded and loaded conditions. The findings suggest that it would be beneficial for these athletes to first decrease their force deficit through mainly maximal strength training before implementing training to further maximize power output. Establishment of the F-v profile could be a useful diagnostic tool for coaches to optimize strength training and to design training intervention based on the individual need of each athlete.